Integrating Human Health into Environmental Impact Assessment: Review of Health Impact Assessment in Thailand - Phayong Thepaksorn; Wattasit Siriwong; Sathirakorn Pongpanich (Applied Environmental Research, 2016)
The objective of this paper is to review the integration of health impact assessment (HIA) into environmental health assessment (EIA) or EHIA, existing legal requirements for health risk analyses, and lessons learned for integrating HIA within EIA processes. The authors undertook literature searches for EHIA practices through academic publications, reports, and websites of public organizations and related agencies in Thailand. We examined and synthesized the HIA system development, regulations, and examples of integrated EHIA. In conclusion, the implementation of EHIA still faces many obstacles, especially in such complex sector policy environments. The uncertainties, lack of evidence base, and challenges in implementing EHIA within the prevailing political and cultural contexts constrain decision-making and remain under-developed. Methodologies and tools have to fit with the available data and resources. The EHIA evaluation requires analytical validity, relevance, stakeholder engagement, and public involvement. The review resulted in the following recommendations to increasing Thailand’s EHIA capacity: 1) develop tools and guidelines for implementation in each project types; 2) train EHIA experts and conduct EHIA courses to build capacity; 3) ensure meaningful participation of private sector and the public; 4) bring together all parties in the debate, and build consensus through community participation and the upholding of environmental justice including EHIA communication; and 5) work to ensure strong public participation and political engagement.